On Chamber-regular C̃₂-Lattices - Stamer, Franziska; Titz Mite, Thomas
We construct the first examples of chamber-regular lattices on C̃₂-buildings. Assuming a conjecture of Kantor our list of examples becomes a classification for chamber-regular C̃₂-lattices on locally-finite C̃₂-buildings. The links of special vertices in the buildings we construct, are all isomorphic to (the incidence graph of) the unique generalized quadrangle Q of order (3,5). In particular our constructions involve chamber-regular actions on Q. These actions on Q are the first (and if Kantor's conjecture holds the only) chamber-regular actions on a finite generalized quadrangle and therefore interesting in their own right. Moreover Q is not Moufang and therefore none of our examples is a Bruhat-Tits building and all our lattices are exotic building lattices.